Konsep Kedisiplinan Pelajar dalam Perspektif Hadis - YN, Mizan; Harmaini, Harmaini (Tadabbur: Jurnal Peradaban Islam, 2025)
This study aims to examine the concept of student discipline from the perspective of hadith as a foundation for character formation and the improvement of Islamic education quality. Using a library research method, this study analyzes both the matan and sanad  of hadiths related to values of discipline in learning, worship, and interaction with teachers and the educational environment. The findings indicate that Islam views discipline as an integral part of moral and spiritual teachings, reflected in the encouragement to use time wisely, seek knowledge earnestly, and maintain proper manners and responsibility in the learning process. Discipline in this context is not limited to academic compliance but encompasses the broader dimension of moral consciousness, self-control, and devotion to Allah. The application of discipline values derived from hadith helps develop students who are not only intellectually competent but also spiritually grounded and socially responsible. Therefore, student discipline represents the internalization of Islamic ethical principles that guide individuals toward balanced, productive, and meaningful lives in accordance with the teachings of the Prophet Muhammad.